Templated growth of poly(p-phenylenevinylene) nanostructures by chemical vapour deposition - Supangat, A.; Bryant, G.; Belcher, W.; Dastoor, P. (Springer Verlag (Germany), 2012)
Poly(p-phenylenevinylene) nanostructures have been successfully synthesised via chemical vapour deposition into a porous alumina template. Poly(p-phenylenevinylene) layers with different textures were created by varying the angle between the template and the precursor gas flow. These different morphologies are characterised by differences in their optical emission spectra, in which the synthesis of these nanostructures opens up perspectives for nanoelectronic devices and sensors application.